The Effect of Using Cellulose Nanofiber from Kapok (Ceiba pentandra, L) as Reinforcement on The Properties of Recycled Papers - Rezekinta, Fransiska Angelina; Kasim, Anwar; Syafri, Edi; Ridwan , Firman; Chaniago , Irawati; Ichiura, Hideaki (Journal of Applied Agricultural Science and Technology, 2024)
Recycling is important for achieving environmentally sustainable products and waste reduction. The trend has led to the addition of reinforcement to recycling process to ensure the effective usage of wasted papers. Therefore, this study was conducted to determine the effect of using cellulose nanofiber (CNF) synthesized from kapok fibers as reinforcement in recycled papers. CNF was applied at different concentrations of 2, 4, 6, 8, and 10% of recycled paper production and the analysis was conducted by testing tensile index, density, and brightness. Moreover, X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and UV-Vis analysis were used to determine the characteristics of the paper. The results showed that CNF addition influenced tensile index, brightness, and density of recycled papers. This was observed from an increase in tensile strength by up to 76.32% and density at approximately 0.58 g/cm3 for 10% CNF addition. Meanwhile, the brightness level was reduced due to the compact nature of paper produced. The trend led to the conclusion that the addition of CNF could impact the characteristics of recycled papers.